An Evaluation of Reported Anti-Tuberculosis Drug Reactions at the DOTS Pharmacy Depot in Al-Ihsan Regional Hospital, West Java - Kharina Septi Lestari; Endah Astri Wijiastuti; Yanni Dhiani Mardhiani (Indonesian Journal of Herbal Science and Innovation, 2025)
Tuberculosis (TB) remained a major public health concern in Indonesia, which ranked second globally after India in TB burden. As TB treatment relied on long-term administration of combined Anti-Tuberculosis Drugs (OAT), patients often experienced treatment challenges, including adverse drug reactions that could reduce adherence and compromise therapeutic success. However, local data regarding the pattern of these reactions—particularly in West Java—had been limited, creating a gap in monitoring practices that were essential for improving patient outcomes. This study aimed to evaluate the types and frequencies of adverse drug reactions reported by TB patients receiving treatment at the DOTS Pharmacy Depot of Al-Ihsan Regional Hospital. This research used a descriptive design with primary data collected from the DOTS Pharmacy Depot. Reported adverse reactions were compiled and analyzed, then presented in tables and graphs to provide a clear overview of the distribution of events. The evaluation focused on patients undergoing Category I OAT therapy during 2023, allowing the study to capture real-world reactions experienced over the course of standard TB treatment. The findings showed that female patients experienced more adverse reactions than males, suggesting potential sex-related differences in susceptibility or reporting. Overall, gastric pain emerged as the most common adverse effect (39.09%), followed by itching (33.04%), headache (11.07%), hyperuricemia (6.64%), nausea and vomiting (5.15%), and epigastric pain (4.13%). These reactions aligned with the known pharmacological profiles of first-line OAT regimens, particularly rifampicin and pyrazinamide, which are commonly associated with gastrointestinal irritation and metabolic disturbances. In conclusion, the study highlighted the urgent need for enhanced pharmacovigilance, early recognition of common adverse reactions, and improved patient education to support treatment adherence. Understanding local patterns of drug reactions provided valuable insights for clinicians and contributed to more effective TB management strategies in West Java.